Illustrated medical biochemistry - Raju, S M (Jaypee Brothers Medical Publishers, 2005)
Biochemistry is a core subject at undergraduate level for all medical and dental students. Equally divided into two sections - general biochemistry and metabolism and biochemical genetics - containing 46 chapters, this is a user-friendly textbook.